Non-Profit Nature of Associations (Vereniging) - Paula Paula (Universitas Airlangga, 2019)
Association (vereniging) is regulated briefly by Indonesia civil code and Stb. 1870 No. 64. There are no restriction on the purpose of establishing an association, other than by law, public order and morality. The purpose of association, which is not to seek profit, or often referred to as a nonprofit goal, is obtained from doctrine. However, there is no common understanding among law experts and practitioners regarding the notion of non profit goal and its implications. On the other hand, the role of associations in society is increasing significantly. The purpose of an association determines the scope of its activity and its governance. Therefore, this research aims to find the purpose and activities of association. This research is a doctrinal research using statue, conceptual, historical, and comparative approach. The result of this research is the term of ‘not to seek profit’ or ‘non-profit’ goal of association should be understood as the purpose other than obtaining profit for - and therefore distributing it to-its members. Associations can engage in profit-making activities as long as it complies with certain restrictions.